CONSERVATIVE AND PROGRESSIVE COMPONENTS IN SCIENCE - Lubański, Mieczysław (Studia Philosophiae Christianae, 2020)
The development of science, proceeding at a higher and higher speed, leads to the creation of new concepts, theories, and ideas. They constitute a progressive component of science. However, scientific development does not mean that everything that was accepted earlier has to be given up. New elements may be acquired and exist together with the old ones. Such old elements constitute a conservative component of science. That is why modern science shows itself as a wholeness constituted by the above-mentioned components.